A prospective study of efficacy and safety of rubber band ligation in the treatment of Grade II and III hemorrhoids – a western Indian experience - Nikam, Vinayak; Deshpande, Aparna; Chandorkar, Iti; Sahoo, Siddharth (Journal of Coloproctology, 2018)
Background Hemorrhoids are one of the most frequent diseases of the anal region with high prevalence involving all age groups. Multiple treatment options exist with none being perfect. Rubber band ligation of hemorrhoids is a non-operative treatment which can be performed on outpatient basis.Objective The study was undertaken to determine efficacy of banding in treatment of Grade II and III hemorrhoids and to follow-up patients treated by banding to evaluate for symptomatic relief, recurrence and complications.Study design A prospective, interventional study with clearance from the institutional ethics committee was undertaken over the period of 2 years in a tertiary referral center with a sample size of 60.Result Out of 60 patients, 41 patients (68.30%) had Grade II and 19 patients (31.7%) had Grade III hemorrhoids. At first follow up, success rate for Grade II hemorrhoids was 85% (35/41) as compared to 21% (4/19) in Grade III. The unsuccessful 20 patients were re-banded, however only 2 of them responded to procedure. At the end of 6 weeks, 36 patients with Grade II hemorrhoids (88%) were cured. Failure rate was higher for Grade III hemorrhoids (68.42%, n = 13). Success rate was 86.6% for single hemorrhoid. There were no major complications. Anemia reverted significantly with successful band ligation.Conclusion Rubber band ligation is a simple, safe and effective method for treating symptomatic second and third degree hemorrhoids as an outpatient procedure. It gives better results for Grade II and single hemorrhoids. Recurrence rate after successful band ligation is low.
Keywords: Hemorrhoids; Rectal bleeding; Band ligation; Hemorrhoidectomy